2014
DOI: 10.14814/phy2.12056
|View full text |Cite
|
Sign up to set email alerts
|

Small changes in lung function in runners with marathon-induced interstitial lung edema

Abstract: The purpose of this study was to assess lung function in runners with marathon‐induced lung edema. Thirty‐six (24 males) healthy subjects, 34 (SD 9) years old, body mass index 23.7 (2.6) kg/m2 had posterior/anterior (PA) radiographs taken 1 day before and 21 (6) minutes post marathon finish. Pulmonary function was performed 1–3 weeks before and 73 (27) minutes post finish. The PA radiographs were viewed together, as a set, and evaluated by two experienced readers separately who were blinded as to time the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
5
21
0
Order By: Relevance
“…Similar increases in extravascular lung water have previously been described in outdoor environments in athletes immediately after both intense and prolonged exercise [18, 20] and in trekkers during high-altitude exposure with and without exercise [19, 53]. …”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar increases in extravascular lung water have previously been described in outdoor environments in athletes immediately after both intense and prolonged exercise [18, 20] and in trekkers during high-altitude exposure with and without exercise [19, 53]. …”
Section: Discussionsupporting
confidence: 69%
“…In the present study, the lung echo assessment was performed immediately after the descent, but we do not think that this timing affected the results. In fact, it has been reported that the radiographic evidence of mild interstitial edema persists for at least one and a half hours post-marathon [20]. Also the development of asymptomatic interstitial lung edema can be involved in the decrease in lung volumes, as previously reported in athletes after an ultramarathon [20].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As previous studies demonstrate, during and immediately after running, MUMs induce cardiac (Maufrais et al, 2016) and neuromuscular (Saugy et al, 2013) fatigue, lung functions alterations as pulmonary ventilations (Vernillo et al, 2015) as well as impairment in postural control (Degache et al, 2014). In parallel, an increase in total body water (Knechtle et al, 2008), in volumes of athletes' body extremities (e.g., feet) (Bracher et al, 2012) and the development of peripheral oedema have been identified (Zavorsky et al, 2014). Blood biomarkers changes also confirm this response, showing higher C-reactive protein concentrations (Millet et al, 2011a; Saugy et al, 2013) and decreased hematocrit levels in runners right after MUMs (Robach et al, 2014; Vitiello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is currently a debate as to whether to assume an infinite or finite θ NO when calculating alveolar-capillary membrane conductance (Dm CO ) and pulmonary-capillary blood volume (V C ) from measures of lung diffusing capacity for CO (DLCO) and NO (DLNO). While our laboratory has consistently held the original assumption that θ NO is effectively infinite, other groups have begun applying a finite value for θ NO of 4.5 ml CO /min/mmHg/ml blood measured via an in vitro study and supported by animal and human studies not designed to calculate an exact θ NO value (Borland and Cox, 1991; Borland et al, 2010; Guenard et al, 2016; Zavorsky et al, 2014). Based on this limited work, a task force has recently recommended the use of a finite θ NO ; however, we believe these recommendations, including those concerning θ NO and also the correct Dm NO /Dm CO ratio, are premature (Zavorsky et al, 2017).…”
Section: Introductionmentioning
confidence: 99%